2023
DOI: 10.4236/as.2023.142015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Suitability of Irrigation Scheduling Decision Support Systems for Lowland Rice Farmers in Sub-Saharan Africa—A Review

Abstract: Irrigation in lowland rice production systems in Sub-Saharan Africa (SSA) is mainly based on traditional surface irrigation methods with continuous flooding practices. This irrigation method ends up using a lot more water that would have otherwise been used to open more land and be used in other water-requiring sectors. Various studies suggest Alternate Wetting and Drying (AWD) as an alternative practice for water management that reduces water use without significantly affecting yield. However, this practice h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
(77 reference statements)
0
4
0
Order By: Relevance
“… [ 70 ] Sprinkler irrigation approach for rice cultivation. [ 75 ] 2 Alternate wetting and drying (AWD) [ 12 , 76 ] Soil water potential (SWP) [ 38 , 77 ] Mulching cultivation without flooding [ 78 , 79 ] Aerobic rice system [ 48 ] Optimal irrigation regimen (OIR) [ 75 ] Saturated soil culture (SSC) [ 80 ] Field water level (FWL) [ 75 ] Intermittent drainage (ID) [ 81 ] Leaching and flushing methods (LFM) …”
Section: Different Water Management Practices For Rice Cultivationmentioning
confidence: 99%
“… [ 70 ] Sprinkler irrigation approach for rice cultivation. [ 75 ] 2 Alternate wetting and drying (AWD) [ 12 , 76 ] Soil water potential (SWP) [ 38 , 77 ] Mulching cultivation without flooding [ 78 , 79 ] Aerobic rice system [ 48 ] Optimal irrigation regimen (OIR) [ 75 ] Saturated soil culture (SSC) [ 80 ] Field water level (FWL) [ 75 ] Intermittent drainage (ID) [ 81 ] Leaching and flushing methods (LFM) …”
Section: Different Water Management Practices For Rice Cultivationmentioning
confidence: 99%
“…Although experiments on rice production under micro-irrigation systems (drip irrigation and sprinkler systems) are promising, traditional surface irrigation with continuous flooding practices and significant water consumption remains widely dominant in rice culti-vation for a number of reasons [121][122][123]. First, rice cultivation under surface irrigation is an ancestral practice and abandonment of this practice is constrained by socio-psychological barriers [124].…”
Section: Water-saving Irrigation Practices For Rice Productionmentioning
confidence: 99%
“…According to research [126][127][128][129][130], there are multiple water-saving technologies, including alternate wetting and drying (AWD), soil water potential (SWP), non-flooded mulching cultivation, aerobic rice system (ARS), efficient irrigation regime (EIR), saturated soil culture (SSC), field water level (FWL), intermittent drainage (ID), leaching and flushing methods (LFM), conventional flooding-midseason drainage-flooding irrigation (FDF), etc. The most popular water-saving technologies developed for rice production systems is the alternate wetting and drying (AWD) [121,123]. Islam et al [121] reported that, according to several authors, AWD entails intermittent irrigation events with intervals of non-flooding, wherein the water level drops below the soil surface between each irrigation, and this saves irrigation water by a range of 7-33% without significant impact on yield compared to conventional flooding.…”
Section: Water-saving Irrigation Practices For Rice Productionmentioning
confidence: 99%
See 1 more Smart Citation